Three Realizations and Comparison of Hardware for Piezoresistive Tactile Sensors - Vidal-Verdú, Fernando; Oballe-Peinado, Óscar; Sánchez-Durán, José Antonio; Castellanos-Ramos, Julián; Navas-González, Rafael Jesús (MDPI, 2001)
Tactile sensors are basically arrays of force sensors that are intended to emulate the skin in applications such as assistive robotics. Local electronics are usually implemented to reduce errors and interference caused by long wires. Realizations based on standard microcontrollers, Programmable Systems on Chip (PSoCs) and Field Programmable Gate Arrays (FPGAs) have been proposed by the authors for the case of piezoresistive tactile sensors. The solution employing FPGAs is especially relevant since their performance is closer to that of Application Specific Integrated Circuits (ASICs) than that of the other devices. This paper presents an implementation of such an idea for a specific sensor. For the purpose of comparison, the circuitry based on the other devices is also made for the same sensor. This paper discusses the implementation issues, provides details regarding the design of the hardware based on the three devices and compares them.
Keywords: Transductores de presión; Tactile sensors hardware; Direct connection sensor-FPGA; PSoC